Effect of n-Butanol on Chromosomal Damage in Mice Bone Marrow Cells - Mansouri, Nahid; Haddad, Farhang; Fereidoni, Masoud; Pourkaveh, Bita (Novelty in Biomedicine, 2016)
Background: n-Butanol is a four-carbon alcohol used widely in foods, cosmetics industries, biology and chemistry research laboratories, and other fields. Long time-effects of inhalation or consumption of small amounts of Butanol on human health are still unknown. On the other hand, numerous reports about the development of n-Butanol toxicity are available. The main objective of the study was to investigate the effects of inhaled and oral administration of n-Butanol as a long-term in vivo investigation. Materials and Methods: Small white laboratory, male mice (20-30 g) were used in 11 groups (n=4) including experimental 1 to 6, 1 to 4 control "A” and positive control groups. Experimental groups 1-3, for 10, 20, and 40 days; 5 hours a day were inside a box with ventilation facilities exposed to air saturated with n-Butanol vapor. Experimental groups 4 to 6, received water containing n-Butanol 0.2%, 1% and 5% for 10 days. Control groups B, 1 to 3 was placed for 10, 20, and 40 days inside a similar box exposed to normal air, respectively. Control group B 4 received water without any particular substance for 10 days. The positive control group received 30µl subcutaneous vinblastine. Bone marrow cells were extracted 24 hours after treatments and stained by May-Grünwald-Giemsa staining and the number of micronucleus was counted. Vinblastine, as a positive control, increased an average of micronucleus numbers significantly compared to control group (P<0.001). Results: n-Butanol inhalation caused no significant difference in 1-3 experimental groups in the average numbers of micronucleus compared to control group, even in the 40 days treatment group, average numbers of micronucleus was decreased comparing to control group (P<0.05). Also, oral administration of 0.2% and 1% n-Butanol had no effect on the average micronucleus numbers compared to the control group, while oral administration of 5% n-Butanol caused even decrease in average numbers of micronucleus compared to control group (P<0.05). Conclusion: n-Butanol inhalation may not cause chromosome damages in rat bone marrow cells that probably is due to its very fast metabolism and decomposition in the body. Therefore, the amount of n-Butanol in the systemic circulation and tissues is very low and, probably, the damaging potential is decreased.